Concurrent Hepatitis C and B Virus and Human Immunodeficiency Virus Infections Are Associated With Higher Mortality Risk Illustrating the Impact of Syndemics on Health Outcomes. (13th August 2020) - Butt, Zahid A; Wong, Stanley; Rossi, Carmine; Binka, Mawuena; Wong, Jason; Yu, Amanda; Darvishian, Maryam; Alvarez, Maria; Chapinal, Nuria; Mckee, Geoff; Gilbert, Mark; Tyndall, Mark W; et al.
Abstract: Background: Hepatitis C virus (HCV), hepatitis B virus (HBV), and human immunodeficiency virus (HIV) infections are associated with significant mortality globally and in North America. However, data on impact of concurrent multiple infections on mortality risk are limited. We evaluated the effect of HCV, HBV, and HIV infections and coinfections and associated factors on all-cause mortality in British Columbia (BC), Canada. Methods: The BC Hepatitis Testers Cohort includes 1.7 million individuals tested for HCV or HIV, or reported as a case of HCV, HIV, or HBV from 1990 to 2015, linked to administrative databases. We followed people with HCV, HBV, or HIV monoinfection, coinfections, and triple infections from their negative status to date of death or December 31, 2016. Extended Cox proportional hazards regression was used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for factors associated with all-cause mortality. Results: Of 658 704 individuals tested for HCV, HBV, and HIV, there were 33 804 (5.13%) deaths. In multivariable Cox regression analysis, individuals with HCV/HBV/HIV (HR, 8.9; 95% CI, 8.2–9.7) infections had the highest risk of mortality followed by HCV/HIV (HR, 4.8; 95% CI, 4.4–5.1), HBV/HIV (HR, 4.1; 95% CI, 3.5–4.8), HCV/HBV (HR, 3.9; 95% CI, 3.7–4.2), HCV (HR, 2.6; 95% CI, 2.6–2.7), HBV (HR, 2.2; 95% CI, 2.0–2.3), and HIV (HR, 1.6; 95% CI, 1.5–1.7). Additional factors associated with mortality included injection drug use, problematic alcohol use, material deprivation, diabetes, chronic kidney disease, heart failure, and hypertension. Conclusions: Concurrent multiple infections are associated with high mortality risk. Substance use, comorbidities, and material disadvantage were significantly associated with mortality independent of coinfection. Preventive interventions, including harm reduction combined with coinfection treatments, can significantly reduce mortality. Abstract : A large population-based cohort was used to document a high mortality risk among individuals with HCV, HIV, and HBV infections, injection drug use, comorbidities, and material deprivation. Harm reduction initiatives coupled with treatment of comorbidities and coinfections can reduce mortality.